PROCESSING OF FLY ASH & BOTTOM ASH IN THE MANUFACTURING OF PAVING BLOCKS TO REDUCE THE TOTAL POLLUTION OF NON-B3 WASTE AT PLTU NAGAN RAYA - Rida Ari Ami; Susy Sriwahyuni (RADJA PUBLIKA, 2022)
Industrial waste remains a problem in today's industrial era. The rapid development of industry has led to an increase in solid, liquid and gaseous wastes. Fly ash and bottom ash (FABA) are solid wastes from coal combustion. In this study, the authors wanted to know how to utilize fly ash and bottom ash solid waste in the manufacture of paving blocks in order to reduce non-B3 waste pollution by combining cement as the adhesive material. This research is descriptive with a qualitative approach, the data collection method is obtained through direct interviews with environmental operators who are responsible for the manufacture of paving blocks, and the data is taken from the PLTU Nagan Raya document. The results showed that the operational activities of PLTU Nagan Raya produce 60-70 tons of fly ash and 8-10 tons of bottom ash per day in the form of solid waste in one operating unit. Temporary Storage Area (TPS) Fly ash and bottom ash are coated with High-Density Polyethylene (HDPE), and Geonet. The results of the research suggest that the use of fly ash and bottom ash should not only be used in the manufacture of paving blocks and internal materials, but also in the manufacture of other external building materials, so as to reduce the amount of non-B3 waste at PLTU Nagan Raya.